Crystal structure of 6-hydroxy-4,8,11b-trimethyltetradecayhdro-8,11-epoxy-6a,9-methanocyclohepta[a]naphthalene-4-carboxylic acid – methanol (1/1), C20H30O4 - Zou Juan (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C20H30O4, orthorhombic, P21212 (no. 18), a = 12.6727(4) Å, b = 19.8422(7) Å, c = 7.5471(3) Å, V = 1897.75(12) Å3, Z = 2, Rgt(F) = 0.0448, wRref(F2) = 0.1311, T = 243(2) K.